2022
DOI: 10.3390/genes13030504
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Aspects of Phelan–McDermid Syndrome: An Interdisciplinary Approach to Management

Abstract: Phelan–McDermid syndrome (PMS) is a rare, heterogeneous, and complex neurodevelopmental disorder. It is generally caused by a heterozygous microdeletion of contiguous genes located in the distal portion of the long arm of chromosome 22, including the SHANK3 gene. Sequence variants of SHANK3, including frameshift, nonsense mutations, small indels and splice site mutations also result in PMS. Furthermore, haploinsufficiency in SHANK3 has been suggested as the main cause of PMS. SHANK3 is also associated with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(136 reference statements)
0
8
0
2
Order By: Relevance
“…Por último, el presente estudio sólo informó de la presencia de la deleción y de la mutación del gen SHANK3 en relación con los diagnósticos de los niños ( Tabla 3 ). Sería útil contar con detalles adicionales sobre el tamaño de la deleción, ya que algunos estudios 8, 56 sugieren que las deleciones más grandes se correlacionan con una discapacidad más grave y esto puede influir en la experiencia de los progenitores. Por el contrario, Cammarata‐Scalisis et al 56 , Ziats et al 57 y Phelan & McDermid 58 dicen que hay una falta general de correlación entre el tamaño de la deleción terminal y el fenotipo.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Por último, el presente estudio sólo informó de la presencia de la deleción y de la mutación del gen SHANK3 en relación con los diagnósticos de los niños ( Tabla 3 ). Sería útil contar con detalles adicionales sobre el tamaño de la deleción, ya que algunos estudios 8, 56 sugieren que las deleciones más grandes se correlacionan con una discapacidad más grave y esto puede influir en la experiencia de los progenitores. Por el contrario, Cammarata‐Scalisis et al 56 , Ziats et al 57 y Phelan & McDermid 58 dicen que hay una falta general de correlación entre el tamaño de la deleción terminal y el fenotipo.…”
Section: Resultados Y Discusiónunclassified
“…Sería útil contar con detalles adicionales sobre el tamaño de la deleción, ya que algunos estudios 8, 56 sugieren que las deleciones más grandes se correlacionan con una discapacidad más grave y esto puede influir en la experiencia de los progenitores. Por el contrario, Cammarata‐Scalisis et al 56 , Ziats et al 57 y Phelan & McDermid 58 dicen que hay una falta general de correlación entre el tamaño de la deleción terminal y el fenotipo.…”
Section: Resultados Y Discusiónunclassified
“…Notably, both Aripiprazole and Risperidone, the only drugs approved so far from the FDA for ASD, act, even if with different mechanisms, pleiotropically on D2 and serotonin receptors. Both drugs were reported as effective against irritability and stereotypical behavior in idiopathic autism ( 71–73 ) and also proved effective in patients with Phelan-McDermid syndrome ( 74 , 75 ) and Fragile-X syndrome ( 76 , 77 ). As our results highlight, we found a significant increase of D2 receptor density in the VS at adulthood in the BTBR and Shank3b lines.…”
Section: Discussionmentioning
confidence: 99%
“…39 Finally, the present study only reported the presence of deletion and SHANK3 gene mutation regarding the children's diagnoses (Table 3). Additional details about deletion size would be useful because some studies 8,56 suggested that larger deletions correlate to more severe disability and this may influence the parental experience. In contrast, Cammarata-Scalisi et al, 56 Ziats et al, 57 and Phelan and McDermid 58 stated that there is a general lack of correlation between terminal deletion size and phenotype.…”
Section: Family's Financial Situationmentioning
confidence: 99%